Quality of life evaluation in the patients with peri-implant mucositis treated with the probiotics - Ахмедбейли, Джавид Рамизович (Actual Dentistry, 2019)
The purpose of this study was to provide an objective assessment of the frequency of medication prescription by dental professionals and determine the effectiveness of the oral probiotics for the treatment and prevention of peri implant mucositis based on the clinical evaluation and OHIP-14 life quality questionnaire. Twenty-one patients in test group received professionally plaque removal plus probiotic (Enteflavin® 4 g) once a day during 1 month, whereas 21 patients in control group received professionally plaque removal only. Clinical evaluation was carried out using a modified implant hygiene index (IGIM). Oral Health-Related Quality of Life quality of life of patients was evaluated by the specialized dental questionnaire OHIP-14. The use of probiotics in the treatment of peri-implant mucositis led to reliable and long-term stability of peri-implant health, as well as to a significant improvement in the quality of life of patients in terms of all parameters of a specialized dental questionnaire. Key words: dental implants, complications, peri-implant mucositis, probiotic, oral health-related quality of life.